Dispatching and scheduling of a complex epuck- based material handling system - Hsu Kyi, Swe Zin (2016)
This project aims to develop a graphic user interface , GUI (i.e. user- friendly tool) that allows the users to control a complex e-puck based material handling system easily by applying distributed routing and scheduling algorithms to the e-puck system in which a given set of transportation tasks to be carried out in minimum execution time. There are four main parts in this system namely GUI, Controller, Schedulers and Short- est path generator (Python). The overview of the system is to allow the e-pucks to carry out a list of loading and unloading tasks with user defined task locations. Based on the tasks assigned to the e-pucks, the shortest and efficient route for each e-puck to com- plete the task list will be generated using shortest path generator program. The path information and the activated e-pucks robots list will then be loaded into con- troller and three schedulers programs via GUI. The GUI will extract the path and com- municate the controller. Hence, controller will connect schedulers to decide the moving time for each e-puck in order to avoid unnecessary waiting time and collision. The gantt chart display is also included in GUI to help the user to track the running time of tasks during the process. Furthermore, the GUI has been programmed as a soft coded program in order to allow the users to make dynamic changes for the system such as the list of available robots with specific e-pucks used according to user requirements. Hence, the GUI is compat- ible for different type of system since it will automatically adjust the application inter- face for users.